STUDIES ON THE CONSTITUENTS OF HIBISCUS ROSA-SINENSIS - Hossain, M Amzad; Tarafdar, S A (Biological Sciences - PJSIR, 2003)
A new flavone derivative. furnaoflavone (1) was isolated along ith ovalichalcone (2) from the lea,cs and stems of llibiscus rosa-si11e11sis (Malvaccac). The structure of funmotlavonc (1) was identilicd as 5-methoi,.-y-3’ -mcth) 1-3’.4,. 111cthylc11cd1oxyfura110[2" , 3":7,8]flavone by spectroscopic und chemical analysis.